2016
DOI: 10.1175/mwr-d-15-0412.1
|View full text |Cite
|
Sign up to set email alerts
|

Lake-Effect Mode and Precipitation Enhancement over the Tug Hill Plateau during OWLeS IOP2b

Abstract: Improved understanding of the influence of orography on lake-effect storms is crucial for weather forecasting in many lake-effect regions. The Tug Hill Plateau of northern New York (hereafter Tug Hill), rising 500 m above eastern Lake Ontario, experiences some of the most intense snowstorms in the world. Herein the authors investigate the enhancement of lake-effect snowfall over Tug Hill during IOP2b of the Ontario Winter Lake-effect Systems (OWLeS) field campaign. During the 24-h study period, total liquid pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 63 publications
1
36
0
Order By: Relevance
“…The IOP2b event was one of the more intense, deep, and long-lived LLAP events encountered in OWLeS (Minder et al 2015;Frame et al 2015;Campbell et al 2016). A precipitation maximum [27 mm of snow water equivalent (SWE) in 12 h] occurred on the Tug, about 40 km downwind of the shore of Lake Ontario on 11 December 2013, according to National Centers for Environmental Prediction (NCEP) stage-IV data (Fig.…”
Section: The Llap Band Of 11 December 2013mentioning
confidence: 99%
“…The IOP2b event was one of the more intense, deep, and long-lived LLAP events encountered in OWLeS (Minder et al 2015;Frame et al 2015;Campbell et al 2016). A precipitation maximum [27 mm of snow water equivalent (SWE) in 12 h] occurred on the Tug, about 40 km downwind of the shore of Lake Ontario on 11 December 2013, according to National Centers for Environmental Prediction (NCEP) stage-IV data (Fig.…”
Section: The Llap Band Of 11 December 2013mentioning
confidence: 99%
“…Niziol (1987) described how the synoptic environment-with regards to the existence of cyclonic vorticity advection at 850, 700, and 500 hPa-contributes to ascent aiding in LES band formation. Campbell et al (2016) detailed how the greatest snowfall rates were produced by LES bands that were accompanied by the passage or approach of upper-level short-wave troughs. Hjelmfelt (1990) found that forced orographic ascent enhances LES intensity.…”
Section: Introductionmentioning
confidence: 99%
“…NCAR operated a NOAH-II at GLE and BTL during 2012, and coauthors (Campbell and Steenburgh) operated a NOAH-II at OWL (December 2013 to January 2014; Campbell et al, 2016). The three NOAH-II gauges were outfitted with Alter shields (Goodison et al, 1998;hereafter G98).…”
Section: Noah-ii Gaugementioning
confidence: 99%
“…4.7.1). Wind speeds used in that calculation are from the hotplate (at GLE and BTL) or from an anemometer (at OWL) (Campbell et al, 2016). Of course, we are assuming that the function from G98 mimics undercatch by our 12 inch (0.30 m; diameter) Alter-shielded NOAH-II gauge.…”
Section: Snow Particle Catch Efficiencymentioning
confidence: 99%
See 1 more Smart Citation